2018
DOI: 10.4103/aja.aja_35_17
|View full text |Cite
|
Sign up to set email alerts
|

Proton-pump inhibitor use does not affect semen quality in subfertile men

Abstract: Proton-pump inhibitors (PPIs) are among the most widely used drugs worldwide. PPI use has recently been linked to adverse changes in semen quality in healthy men; however, the effects of PPI use on semen parameters remain largely unknown specifically in cases with male factor infertility. We examined whether PPI use was associated with detrimental effects on semen parameters in a large population of subfertile men. We retrospectively reviewed data from 12 257 subfertile men who had visited our fertility clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…In another study, the investigators included 40 sub fertile men taking medication for gastric acid related symptoms and compared the semen parameter to control. No signifi cant difference was found in semen parameters between cases and controls [18]. Which is matched to our study in which only semen volume signifi cantly decreased p 0.05.…”
Section: Discussionsupporting
confidence: 81%
“…In another study, the investigators included 40 sub fertile men taking medication for gastric acid related symptoms and compared the semen parameter to control. No signifi cant difference was found in semen parameters between cases and controls [18]. Which is matched to our study in which only semen volume signifi cantly decreased p 0.05.…”
Section: Discussionsupporting
confidence: 81%
“…Later study on male mice, in 2002, demonstrated that omeprazole did not induce the increase in diploid or disomic sperm (Adler, Schmid, & Baumgartner, ). A very recent retrospective data review on 248 subfertile men who used proton pump inhibitors for at least 3 months before semen collection concluded that, in general, proton pump inhibitors, including omeprazole, did not associate with determinantal effects on semen quality (Keihani et al, ). Alternatively, seminal Helicobacter pylori treatment (500 mg tinidazole, 250 mg clarithromycin and 20 mg omeprazole) twice a day, for 14 days, was found to improve progressive and total sperm motility in asthenozoospermic males (Caviglia, Fagoonee, & Pellicano, ; El‐Garem, El‐Sawy, & Mostafa, ).…”
Section: Discussionmentioning
confidence: 99%
“…Only two recent studies investigated the effect of PPI intake in a period > 3 months preceding semen analysis on human semen quality. The results were clearly contradictory, the first showing that the use of PPIs is associated with a threefold higher risk of low total motile sperm count, 41 whereas the second has shown PPI use was not associated with detrimental effects on conventional semen parameters in subfertile patients 42 . However, these studies revealed only one facet of sperm inhibition by PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…The results were clearly contradictory, the first showing that the use of PPIs is associated with a threefold higher risk of low total motile sperm count, 41 whereas the second has shown PPI use was not associated with detrimental effects on conventional semen parameters in subfertile patients. 42 However, these studies revealed only one facet of sperm inhibition by PPIs. Spermatozoa can indeed be modulated either in the male by PPIs while they are produced in the testis or stored in the epididymis or in the female when they are located in the uterus and oviduct.…”
Section: Discussionmentioning
confidence: 99%